Pediatric and adult sonic hedgehog medulloblastomas are clinically and molecularly distinct - Northcott, Paul A.; Hielscher, Thomas; Dubuc, Adrian; Mack, Stephen; Shih, David; Remke, Marc; Al-Halabi, Hani; Albrecht, Steffen; Jabado, Nada; Eberhart, Charles G.; Grajkowska, Wieslawa; Weiss, William A.; et al. (Acta neuropathologica, 2011)
Recent integrative genomic approaches have defined molecular subgroups of medulloblastoma that are genetically and clinically distinct. Sonic hedgehog (Shh) medulloblastomas account for one-third of all cases and comprise the majority of infant and adult medulloblastomas. To discern molecular heterogeneity among Shh-medulloblastomas, we analyzed transcriptional profiles from four independent Shh-medulloblastoma expression datasets (n = 66). Unsupervised clustering analyses demonstrated a clear distinction between infant and adult Shh-medulloblastomas, which was reliably replicated across datasets. Comparison of transcriptomes from infant and adult Shh-medulloblastomas revealed deregulation of multiple gene families, including genes implicated in cellular development, synaptogenesis, and extracellular matrix maintenance. Furthermore, metastatic dissemination is a marker of poor prognosis in adult, but not in pediatric Shh-medulloblastomas. Children with desmoplastic Shh-medulloblastomas have a better prognosis than those with Shh-medulloblastomas and classic histology. Desmoplasia is not prognostic for adult Shh-medulloblastoma. Cytogenetic analysis of a large, non-overlapping cohort of Shh-medulloblastomas (n = 151) revealed significant over-representation of chromosome 10q deletion (P < 0.001) and MYCN amplification (P < 0.05) in pediatric Shh cases compared with adults. Adult Shh-medulloblastomas harboring chromosome 10q deletion, 2 gain, 17p deletion, 17q gain, and/or GLI2 amplification have a much worse prognosis as compared to pediatric cases exhibiting the same aberrations. Collectively, our data demonstrate that pediatric and adult Shh-medulloblastomas are clinically, transcriptionally, genetically, and prognostically distinct.
Gesehen am 29.09.2022